Adaptive input shaping for sway control of 3D crane using a pole-zero cancellation method - Abdullahi, Auwalu M.; Mohamed, Zaharuddin; Zainal Abidin, Mohamad Shukri; Akmeliawati, Rini; Husain, Abdul Rashid; A. Bature, Amir (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents an adaptive input shaping based on pole-zero cancellation (APZC) technique to suppress load sway of a crane system. In this method, a reference system is selected and the proposed adaptive shaper is made to force the actual system to adapt to the changes in natural frequency and damping ratio as the cable length increases or decreases. Simulation results are compared with a zero vibration derivative input shaper designed based on average travel length (ATL) to investigate the performance of the proposed shaper. Simulation using three cable length of 0.7 m, 0.5 m and 0.3 m shows that APZC gives better payload sway reduction with smallest maximum sway